A plant‐functional‐type approach tailored for stakeholders involved in field studies to predict forage services and plant biodiversity provided by grasslands. (2nd June 2014) - Duru, M.; Jouany, C.; Theau, J. P.; Granger, S.; Cruz, P.
Abstract The plant‐trait‐based method is powerful for assessing ecosystem services provided by species‐rich grasslands, but its use presents difficulties for stakeholders involved in field studies. Therefore, we examined whether a simplified plant‐functional‐type method could overcome such difficulties. A total of 1287 grasslands, spread over eight regions, were characterized according to their environmental and management factors, eight indicator (including Ellenberg) values and abundance of five previously defined grass functional types (GFTs) differing in growth strategies (fast–slow, early–late). Four related plant‐community‐composition descriptors indicating forage services (forage production, digestibility, distribution of herbage biomass throughout the growing season and management flexibility) responded to environmental and management factors that are correlated to indicator values. Based on GFTs, cluster analysis defined vegetation types (VTs). Their relationships to environmental and management factors (or proxies of them), forage services and species richness were subsequently analysed. Of the thirteen VTs, four consisted mainly of GFTs with a dominant fast‐growth strategy and three with a slow‐growth strategy. These clusters were clearly related to two stress axes (temperature and nutrients). The other six VTs consisted of a mixture of both strategies and corresponded to intermediate levels of stress and disturbance. Although simplified, the method distinguished VTs that responded consistently to environmental and management factors and provides accurate indicators of forage services.